Mechanical properties of SiOx gas barrier coatings on polyester films - Howells, D; Henry, B; Leterrier, Y; Manson, J; Madocks, J; Assender, H (2008)
This paper reports the impressive mechanical properties of 1 μm thick carbon-containing SiOx gas barrier coatings, characterised using the uniaxial fragmentation test. Such coatings have been found to act as excellent barriers to water vapour permeation partly because they can be made so thick without stress induced cracking. The impressive mechanical properties are thought to be due in part to the high amount of carbon they contain, which gives them a more organic character, as well as the fact that they are deposited as a succession of thinner layers. The adhesion of the coatings to the polyester film is good in all cases, reflecting a high density of covalent bonding at the interface. Improvement of the mechanical properties of a SiOx/PET composite can be achieved by altering the substrate. By replacing the PET with a heat-stabilised (HS) PET film, a HS film with an acrylate layer or PEN, it is found that the coating displays improved mechanical properties and adhesive strength (as well as barrier). This is thought to be due to the superior surface thermal and mechanical properties of these substrates. Deposition temperatures are at least 80 °C, which causes molecular motion at the surface of a plain PET film and creates defects in the SiOx coating as it grows, making it more brittle and permeable to gas flow. © 2008 Elsevier B.V. All rights reserved.